Employer branding as a talent management tool: A systematic literature revision - Reis, I. (2021)
The aim of this paper is to present a systematic literature revision (SLR) that shows the relationship between the concept of employer branding (EB) and talent management (TM). Based on the EB model proposed by Backhaus and Tikoo in 2004, and the macro-contingent model for talent management introduced in 2019 by King and Vaiman, we intend both to analyse the theory correlating the EB concept and TM, and to identify TM dimensions that are reflected on the EB concept. A systematic literature revision was carried out using the Preferred Reporting Items for Systematic Reviews (PRISMA) protocol in order to identify and sum up the most relevant studies of the last 10 years concerning these topics. Findings show that scientific literature on the subject grew considerably in the last four years, reflecting the rising concern over the creation of an employer brand at the organisational level. EB explores talent attraction and retention particularly, though, unexpectedly, is also becoming a concept explored by nations to attract a qualified workforce. Analysing selected articles, we may conclude that EB is clearly considered as a tool within the largest process of talent management.